(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
Origin of the book: A thesis submitted in fulfillment of the requirements for the PhD Degree in regulations, College of Sharia, the Islamic University of Madinah Waqf: It means that the asset is blocked from taking part in any commercial transaction, while its yields are devoted to charitable purposes. The Saudi legislator did not define the waqf in its singular form, but rather defined it with its various types: public, private and joint waqf. Similar terms for waqf are endowment - charitable trust - foundation. All of these are about donating and providing aid, and are based on properties being invested, so that the return could be spent on what was set up for it. The term charitable trust is the closest meaning to the waqf, and its elements are like the elements of the waqf in general. The Trust Law defines the Trust as: a means of managing such assets as money, investments, land and buildings on behalf of people. A Trust has three elements: Trustor; the person who appoints the Trust’s property and determines how it will be used. The properties of the waqf are recorded in the document. Trustee; the person who manages the Trust. Beneficiary; the person who benefits from the Trust. Among the advantages of the Trust are: exemption from tax; acquiring legal force to register it with the Commission; high legal protection; ease of dismissing the negligent trustee or traitor through a decision of the board of trustees, without referring to the judiciary; having grants for the Trust; having financial support from the government; and expansion of charitable work. In Britain, there are 167,443 charitable institutions, and their revenues are seventy-four billion, four hundred and twenty-nine million. This statistic was on September 1, 2017.